PENGARUH KEPEMIMPINAN, KECERDASAN EMOSIONAL DAN IKLIM KERJA TERHADAP KINERJA GURU PNS DI SMP NEGERI 1 KEBUMEN (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
This study aims to determine the effect of leadership, emotional intelligence, and work climate on the performance of civil servant teachers at SMP Negeri 1 Kebumen. The sampling technique used is a saturated sample, which is taking a sample as a whole or all members of the population are used as samples. Respondents in this study were civil servant teachers totaling 35 people. This study uses descriptive and statistical analysis methods to test validity, reliability test, multicollinearity test, heteroscedasticity test, normality test, multiple linear regression analysis, partial test, simultaneous test, and coefficient of determination. The test in the t test shows that leadership has an effect on the performance of PNS teachers at SMP Negeri 1 Kebumen. Emotional intelligence has no effect on the performance of civil servant teachers at SMP Negeri 1 Kebumen. Work climate affects the performance of PNS teachers at SMP Negeri 1 Kebumen. The test in the f test shows that leadership, emotional intelligence, and work climate together affect the performance of PNS teachers at SMP Negeri 1 Kebumen.
Keywords: Leadership; Emotional Intelligence; Work Climate; Teacher Performance